On nonlinear higher order elliptic systems positive in the first derivatives - Kalita, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Elliptic systems of a divergent type with a natural energy space W^m_p W^l_q are considered. Under certain restrictions imposed on the modulus of ellipticity of the lower part of the system, the Hölder property of the generalized solutions to this system and the Liouville theorem are established.